STRATEGI PENGEMBANGAN PENGELOLAAN FARMASI DAN LAYANAN KESEHATAN TAMBAHAN UNTUK MENINGKATKAN PENDAPATAN RS “X” - Mairosa Nurul Fitriani; Rian Andriani; Kahar Mulyani (Bajang Institute, 2025)
The tight competition in the world of health services and the high number of pending BPJS claims have disrupted the cash flow of ”X” Hospital. So if this is allowed to dissolve, the facilities and infrastructure and management stability will also be disrupted. So this study aims to analyze management, investment and business strategies in pharmaceutical management and additional health services to increase the income of ”X” hospital. This research uses a qualitative design. Informants in this study were 10 respondents. Data collection using interviews, documentation and observation. Based on the results of the research, strategies that can be implemented by ”X” Hospital to increase revenue include 24-hour pharmacy services, strengtening medical check-up and physiotheraphy drug delivery, stock automation, and revenue diversification through paid services. In addition, digital promotion and external cooperation also increase the hospital's competitiveness. The results show that the combination of these strategies can improve operational efficiency and create sustainable revenue. So it can be concluded that the strategy based on the overall evaluation is able to formulate effective and efficient steps in management, investment and business to increase the revenue of ”X” Hospital